2008
DOI: 10.1117/12.778915
|View full text |Cite
|
Sign up to set email alerts
|

Color in perceptual tracking using low frame rate motion imagery

Abstract: A perceptual evaluation compared tracking performance when using color versus panchromatic synthetic imagery at low frame rates. Frame rate was found to have an effect on tracking performance for the panchromatic motion imagery. Color was found to be associated with improved tracking performance at 2 frames per second (FPS), but not at 6 FPS or greater. A self estimate of task confidence given by the respondents was found to be correlated to the measured tracking performance, which supports the use of task con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…3 Subsequent work examined the effects of frame rate, laid out a methodology for development of a motion quality metric, and conducted evaluations using static and dynamic criteria. 4,5,6,7,8,9 A clear conclusion was, "the ability to perform exploitation tasks depends primarily on the spatial resolution". 7 These studies also showed that trained analysts can consistently rank motion imagery based on perceived interpretability, and that analyst self-estimate of task confidence can be used as a surrogate for actual task performance.…”
Section: Niirs Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…3 Subsequent work examined the effects of frame rate, laid out a methodology for development of a motion quality metric, and conducted evaluations using static and dynamic criteria. 4,5,6,7,8,9 A clear conclusion was, "the ability to perform exploitation tasks depends primarily on the spatial resolution". 7 These studies also showed that trained analysts can consistently rank motion imagery based on perceived interpretability, and that analyst self-estimate of task confidence can be used as a surrogate for actual task performance.…”
Section: Niirs Backgroundmentioning
confidence: 98%
“…Experiment has shown that for the common motion imagery task of "visually track" that color did not improve either actual or perceived task performance for sufficient frame rates without occlusions. 9 Of course, color can be a great aid when the task is color specific, or the target has a unique color characteristic that can be used to re-acquire the target when it re-appears after being occluded.…”
Section: Construct Validity Of V-niirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Image blur through the atmosphere results from very small angle forward scattering by aerosols and from optical turbulence 10 . Equation (9) shows that attenuation is a function of the distance, z the scattering coefficient, S, and the attenuation coefficient, A,…”
Section: Increased Distortion Due To Noise Motion Atmosphere and Cmentioning
confidence: 99%